2018
DOI: 10.1016/j.dam.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Computational complexity of distance edge labeling

Abstract: Abstract. The problem of Distance Edge Labeling is a variant of Distance Vertex Labeling (also known as L2,1 labeling) that has been studied for more than twenty years and has many applications, such as frequency assignment. The Distance Edge Labeling problem asks whether the edges of a given graph can be labeled such that the labels of adjacent edges differ by at least two and the labels of edges at distance two differ by at least one. Labels are chosen from the set {0, 1, . . . , λ} for λ fixed. We present a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…from P to NP-complete (indeed, we do not even prove the existence of such a border). The authors of [7] were looking for a more general result, similar to ours, but found the case (p, q) = (2, 1) laborious enough to fill one paper [10]. In fact, their proof settles for us all cases where p ≥ 2q.…”
Section: Regimementioning
confidence: 66%
See 4 more Smart Citations
“…from P to NP-complete (indeed, we do not even prove the existence of such a border). The authors of [7] were looking for a more general result, similar to ours, but found the case (p, q) = (2, 1) laborious enough to fill one paper [10]. In fact, their proof settles for us all cases where p ≥ 2q.…”
Section: Regimementioning
confidence: 66%
“…Reduction from Place in article 2 ≤ q /p NAE-3-SAT Section 3.2 1 < q /p ≤ 2 NAE-3-SAT Section 3.1 q /p = 1 5-COL Section 4 ([9]) 2 /3 < q /p ≤ 1 3-COL Section 5 q /p = 2 /3 1-in-3-SAT Section 6 1 /2 < q /p < 2 /3 2-in-4-SAT Section 7 0 < q /p ≤ 1 /2 NAE-3-SAT Appendix ( [7]) Table 1 Table of results and where to find their proofs.…”
Section: Regimementioning
confidence: 99%
See 3 more Smart Citations